Follistatin Rescues Blastocyst Development of Poor Quality Porcine Cumulus–Oocyte Complexes by Delaying Meiotic Resumption With Decreased cGMP. (May 2018) - Lee, Bo Myeong; Chun, Ju Lan; Lee, Ji Hye; Kim, Eun Young; Park, Kang-sun; Lee, Jin-Hee; Daigneault, Bradford W.; Smith, George W.; Kim, Keun Jung; Chang, Kyu-Tae; Lee, Sang-Rae; Kim, Sun-Uk; et al.
Mammalian oocytes resume maturation when removed from follicles and cultured in vitro. During folliculogenesis, oocytes are bathed in follicular fluid (FF), which provides an important and specialized microenvironment for oocyte competence. Follistatin (FST) is one component of FF that may play a role in oocyte maturation and embryo development. This study was conducted to examine possible effects of FST on porcine oocyte competence and embryo development. Exogenous FST in oocyte maturation medium for 22 or 44 hours did not improve nuclear maturation and had no effect on good quality cumulus–oocyte complexes (COCs). However, FST improved blastocyst rates in embryos derived from oocytes with less than 2 layers of cumulus. Follistatin treatment of the poor quality COC group increased transcript levels for genes indicative of oocyte quality. Transcript levels were also altered for cumulus expansion–related genes in response to FST when measured during the germinal vesicle breakdown stage. Interestingly, high-quality oocytes remained at germinal vesicle stage much longer than low-quality oocytes, FST treatment induced temporary blockage of spontaneous meiotic resumption when added during culture of both good and poor quality COCs, and levels of cyclic guanosine monophosphate (cGMP) were higher in FST-treated versus untreated groups for both good and poor quality oocytes. In conclusion, FST treatment of porcine oocytes during in vitro maturation can rescue competency of poor quality oocytes to develop to blastocyst stage following in vitro fertilization. Beneficial effects of addition of FST to culture medium may be mediated by inhibiting degradation of cGMP and temporarily delaying nuclear maturation.